EFEKTIVITAS PENGGUNAAN SPREADSHEET DALAM PROSES PENGINPUTAN PENGEMBALIAN DAN PENGIRIMAN BUKU TANAH DI ARSIP BPN KOTA BANDUNG - Nasha Rahmi Husna; Haria Saputry Wahyuni (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2026)
The management of land book delivery and return data is an essential component of archival administration at the National Land Agency (BPN) of Bandung City. To improve data organization and efficiency, spreadsheet-based recording has been implemented to support these processes. This study aims to analyze the effectiveness of spreadsheet usage in the data recording process of land book delivery and return at BPN Bandung City. The research employs a qualitative approach, using interviews, observation, and documentation as data collection techniques. Interviews were conducted with one key informant who directly manages the spreadsheet input process and two supporting informants consisting of internship students involved in daily data entry activities. Observations were carried out to understand the workflow of land book delivery and return, while documentation was used to support field findings. The results indicate that the use of spreadsheets contributes positively to administrative order, data accuracy, and work efficiency. Spreadsheet features such as real-time saving and shared access help reduce the risk of data loss and facilitate collaborative data management. The structured data format also supports annual reporting and employee performance evaluation. However, several limitations were identified, including the risk of data overlap due to simultaneous use and dependency on computer performance. Despite these constraints, the current system is considered effective in supporting archival management. Therefore, further development toward an integrated web-based system and improvement of supporting infrastructure are recommended to enhance efficiency, accuracy, and sustainability of land book data management at BPN Bandung City.